Optimizacija vosstanovlenija serdecno-sosudistoj sistemy putem primenenija uprazneni na rastjagivanie skeletnych mysc - Spirin, V. K. (Teorija i Praktika fiziceskoj Kul'tury, 2004)
The methodical approaches for optimization of recovery processes are developed by the application of exercises on the extension of skeletal muscles. It was established, that in the final part of training exercises the performance of 5-10 minute complexes for the extension of skeletal muscles promotes more effective restoration of cardiovascular system. The relaxation of muscles at their extension was an obligatory condition of the performance of these exercises.